Phenomenological Analysis of Consumer Shopping Behavior in Asia and Europe - Iskandarsyah Siregar (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2023)
This analysis is in the form of a conceptual analysis. The purpose of this paper is to find out the differences between Asian and European netizens. Asia and Europe have different numbers of netizens. Netizens in Asia have more numbers than netizens in Europe. Netizens in Asia and European netizens often use smartphones or tablets to buy products. Asia has substantial market potential in online business, while in Europe, several countries still need to improve social delivery networks and services. China, Japan, Korea and Southeast Asia are potential markets in Asia, while Germany, Poland, and Norway are potential markets in Europe. In conclusion, the online shopping behaviour of consumers in Asia and Europe is influenced by various factors, including demographics, cultural differences, payment methods, e-commerce platforms, mobile shopping, and cross-border shopping. Businesses catering to online shoppers need to understand these differences to tailor their marketing strategies and provide a better online shopping experience.